A Distributed Secondary Control Strategy for Power Sharing and Voltage Regulation by Multiple Converters in DC Micro-grids - Ahmed Mohamed, Ahmed Haidar; Shahid, Ullah; Muttaqi, Kashem M; Ahfock, Tony (IEEE, 2019)
Recent research and advancement in DC systems reveal that DC distribution may be an efficient, reliable and economical solution to avoid the inherent issues associated with AC power systems such as frequency control, harmonics and synchronization. However, some key operational issues in DC micro-grids are to ensure a stable output voltage and proper load sharing among the sources. Improper current sharing and voltage variations in the conventional droop control causes circulating currents due to the presence of droop and line resistance between converters. This paper presents a distributed secondary control strategy to smooth the output voltage and maintain power sharing based on average current/voltage control and circulating current minimization. Further, an additional current feedback loop is introduced to modify the micro-grid reference voltage during overload conditions for minimizing the line voltage drop and power losses. The conventional communication links are used for exchanging information to the relevant controllers simultaneously to implement the proposed distributed control. The performance of the proposed approach has been verified by simulating two parallel Buck converters supplying a common load. The effect of load switching on voltage regulation and power sharing has also been analyzed.